ESTIMATION OF TRACE LEVEL OF N-NITROSO FLUOXETINE IMPURITY IN FLUOXETINE CAPSULES BY LC-MS/MS - KUMAR, BHUPINDER; MUDHULKAR, RAJU; VENUGOPALA RAO, DAMA; LODHI, SATEESH SINGH (International Journal of Applied Pharmaceutics, 2026)
Objective: Nitrosamine impurities, particularly nitrosamine drug substance-related impurities (NDSRIs), have gained focus in recent past due to their carcinogenic potential. Due to the low sensitivity of conventional techniques like high-performance liquid chromatography (HPLC) and gas chromatography (GC), the exact levels of these impurities could not be determined. This study aims to develop and validate a sensitive liquid chromatography hyphenated with mass spectrometry (LC-MS/MS) method to estimate the trace levels of N-Nitroso fluoxetine (a fluoxetine-related NDSRI) in fluoxetine capsules (60 mg). Methods: We developed a sensitive and selective LC-MS/MS method for the quantification of trace levels of N-Nitroso fluoxetine in fluoxetine capsules (60 mg) using the AB Sciex 5500+quadrupole ion trap (QTRAP) LC-MS/MS system. To achieve the maximum response at quantitation level for N-Nitroso fluoxetine impurity, chromatographic conditions optimized by selecting a specific combination of column, mobile phase, and diluent. Mobile Phase A and B consisted of 10 mmol ammonium acetate buffer and methanol, respectively. Waters X-Bridge C18 column (250 × 4.6 mm, 3.5 μm, Part No. 186003943) at temperature 40 °C and mobile phase flow rate to 0.5 ml/min has yielded consistent results by employing an optimized gradient elution program (Tmin/%B): 0/75, 2/75, 16/95, 28/98, 28.1/75, and 35/75 for the analysis. To further maximize the response of the N-Nitroso fluoxetine impurity, the multiple ion reaction monitoring (MRM) mass spectrometry method in positive electron spray ionization (ESI) mode is preferred over single ion monitoring (SIM) method. Results: The newly developed method is validated by performing parameters such as specificity, method precision, intermediate precision, detection limit, quantitation limit, linearity, and accuracy in accordance with the international conference on harmonization (ICH Q2 (R1)) Guidelines. Limit of detection (LOD) and limit of quantitation (LOQ) are established as 0.06 ppm and 0.11 ppm, respectively. The method is found capable to demonstrate accuracy, precision, and linearity across the range of 0.11 to 1.68 ppm (10% to 150% of the specification), where linearity study shows the correlation coefficient (r²) greater than 0.99 for linearity plot between concentration and area. Recovery data at 10%, 50%, 100%, and 150% of the specification levels indicates that the recovered impurity content observed between 80% and 120%. Based on these results, we have successfully established the method for batch analysis of fluoxetine capsules (60 mg). Conclusion: A new rapid and sensitive reverse-phase ultra-high-performance liquid chromatographic (UHPLC) method coupled with a mass spectrometry detector has been developed and validated for the estimation of N-Nitroso fluoxetine impurity in fluoxetine capsules. Method validation is accomplished according to the ICH Q2 (R1) guidelines, assessing parameters such as limit of detection, limit of quantitation, accuracy, precision, and linearity. We found the method suitable for its intended use and successfully applied it to test batches of the fluoxetine capsules drug product.